EVALUATING THE IMPACT OF VITAMIN C ON ORAL HEALTH- A RANDOMISED CONTROL TRIAL - Khader, Anas Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Background: Oral health is an integral part of overall health. Nutrition plays an important role in maintaining oral and hence general health. Vitamin C also known as Ascorbic acid is a water soluble Vitaminwhich plays an important role in maintaining periodontal and oral health. However excessive intake of Vitamin C leads to detrimental oral conditions such as enamel erosion. Hence a balanced intake according to RDA is important.Objectives: The present clinical study was conducted to evaluate the positive as well as the negative aspects of Vitamin C on oral health.Methodology: 170 patients were randomly categorized into 2 groups; Group 1 (n=85): group with normal serum Vitamin C levels and with history of adequate intakeaccording to the Average Requirement valueand Group 2 (n=85): with deficient Vitamin C levels and inadequate intake. Evaluation oforal manifestations and their prevalence was recorded in both the groups by a well experienced oral medicine expert and findings were recorded in terms of gingivitis, periodontitis, petechial, paleness of oral mucosa and dental erosion. Data collected was statistically evaluated.Results:One way ANOVA showed statistically significant difference between two groups where group 2 had significantly more patients with gingivitis and periodontitis as compared to group 1 with mean value of 1.3529±0.5049 & 1.5882±1.208 in group 1 and 1.6118±0.6743 & 2.4353±2.1737 in group 2 for gingivitis and periodontitis respectively.In Group I, 27 subjects reported with enamel erosion, 29 presented with bleeding gums, 4 with established periodontitis. A petechial on buccal mucosa was seen in 1 patient while 2 presented with pale mucosa. In Group II enamel erosion was present in 4 subjects bleeding gums/ gingivitis 50.5% individuals, periodontitis in 17 cases, 02 presented petechial on hard palate and 04 on buccal mucosa.Conclusion: Vitamin C (Ascorbic acid)is an important Vitamin playing key role in maintenance of oral health and works as anti-oxidant (free radical scavenger). Deficiency leads tooral health detriment andoral manifestationscharacterized by delayed wound healing, bleeding, swollen gingiva Pale mucosa was observed 12. However inter group difference between two groups was statistically insignificant (p˃ 0.1).There was increased incidence and development of periodontal disease eventually leading to tooth loss was noted. Adequate and balanced intake of Vitamin Cis advocated for healthy oral cavity.